General Data Protection Regulation in Health Clinics - Lopes, Isabel Maria; Guarda, Teresa; Oliveira, Pedro (Journal of medical systems, 2020)
The focus on personal data has merited the EU concerns and attention, resulting in the legislative change regarding privacy and the protection of personal data. The General Data Protection Regulation (GDPR) aims to reform existing measures on the protection of personal data of European Union citizens, with a strong impact on the rights and freedoms of individuals in establishing rules for the processing of personal data. The GDPR considers a special category of personal data, the health data, being these considered as sensitive data and subject to special conditions regarding treatment and access by third parties. This work presents the evolution of the applicability of the Regulation (EU) 2016/679 six months after its application in Portuguese health clinics. The results of the present study are discussed in the light of future literature and work are identified.